The Influence of Quality of Service and Facilities on Customer Satisfaction at Hotel Grand Inna Medan - Sabhiena, Macfiratul Fahra; Setiono, Agus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study was to analyze how the influence of service quality and facilities on customer satisfaction at the Grand Inna Hotel. The analytical method used in this research is validity and reliability, multiple linear regression test results, coefficient of determination (R2), simultaneous test (f test), and partial test (t test). The sample in this study was 112 people, while the application used to process research data was SPSS 22. The results of the study found that t count > t table was 0.211 < 1.981 and significant value was 0.833 < from alpha 0.05. This means that the quality of service does not have a positive and significant effect on customer satisfaction at the Grand Inna hotel. The results showed that t arithmetic > t table was 2.382 > 1.981 and the significant value was 0.019 < from alpha 0.05. This means that the facilities have a positive and significant effect on customer satisfaction at the Grand Inna hotel. It is proven by the results of the F (simultaneous) test, the calculated F value is 26.655 > the Ftable value is 2.69 and the significant value is 0.000 < from the alpha value of 0.05. The results showed that the variables of Service Quality and Facilities on Consumer Satisfaction had a positive and significant effect simultaneously and partially on Customer Satisfaction at Grand Inna Hotel Medan.